Asymmetric transition metal catalysis toward screw-shaped aromatic compounds - S. Cauteruccio (2023)
The helix is a widespread chiral geometrical form in nature, and its elegant three-dimensional shape can be associated with different natural items (e.g., the spiral shells of molluscs and snails, the vines entwined with trees, or the left-handed helical tusk of the narwhal). Nature has also selected the homochiral topology for its biological systems at microscopic level, such as the two right-handed helices of DNA and the right-handed helical substructures (i.e., the -helices) in many proteins. Thus, helicity is a fundamental element of molecular chirality, and supramolecular interactions between helices are of outmost importance in molecular biology.1 In the chemist’s synthetic world, one remarkable example of helicity is provided by the helicenes, whose name contains both the prefix "helic-", denoting the nonplanar shape, and the suffix "-enes" indicating the presence of unsaturated system. According to the IUPAC rules, helicenes are polycyclic aromatic or heteroaromatic compounds which contain at least five ortho-fused rings that adopt a nonplanar screw-shaped skeleton due to the steric repulsive interaction between the terminal rings. Because of their nonplanarity, these molecules are chiral and, based on the helicity rule proposed by Cahn, Ingold, and Prelog,2 a left-handed helix is designed "minus" and denoted as M while a right-handed one is designed "plus" and denoted P (Figure 1). Helicenes composed by solely carbocyclic aromatic rings in their structure are defined carbohelicenes, whereas heterohelicenes contain at least one heteroaromatic ring in the screw skeleton (Figure 2).3,4 The introduction of heteroatom(s) in the helical framework significantly affects the geometric parameters and the electronic structure of the helix, providing unique functions and chiroptical response.5,6 The inherent chirality in combination with the extended -conjugated system provide helicenes with outstanding chiroptical properties, and they have been proposed in a plethora of cutting-edge applications, including ...